Atlantic Environments and the American South - Johnson, D. Andrew; Earle, Thomas Blake (Book collections on Project MUSE., 2020)
"This anthology places itself at the intersection of Atlantic, environmental, and southern history, pushing for a new "confluence" of scholarship. There is clear overlap in interests and influences for these fields but they have proceeded, largely, on parallel tracks to-date. In their lucid introduction and throughout the collection, an emerging group of historians explore crucial insights that a self-consciously Atlantic environmental history of the American South can offer. By centering this project on a region, the American South-defined as the southeastern reaches of North America and the Caribbean-the authors interrogate ways in which European colonizers, Native Americans, and Africans interacted in and with the (sub)tropics, a place foreign to Europeans"--